KARAKTERISTIK MUTU BUBUK OKARA HASIL KERAGAMAN PERLAKUAN HIDROTERMAL DAN SUHU PENGERINGAN - Iwan Taruna (Faculty of Agricultural Technology, University of Jember, 2019)
The present study aimed to investigate the influences of experimental variables, i.e. hydrothermal treatments (whithout and treated) and convective drying temperatures (70, 80 and 90°C) on the quality characteristics of okara powders. The quality parameters of the okara powder studied in this experiment consisted of color attributes, particle density, water absorption capacity, oil absorption capacity, pH, viscosity, and non-enzymatic browning. The results showed that the quality of okara powders varied depending on the experimental variables. Hydrothermal treatment and drying of okara at lower temperatures could increase the brightness (L value) from 62.37 to 70.23, and increased the b value of okara powder color from 43.65 to 49.16. However, the particle density (1.04-1.35 g/cm3) and pH value (6.48-6.78) of okara powders were not significantly affected by hydrothermal treatment. The okara powder solution with hydrothermal treatment (2.10-4.50 cP) showed a lower average viscosity value compared to okara powder without hydrothermal treatment ((2.60-4.80 cP). The study also concluded that okara powder absorbed significantly more water rather than absorbing oil, as indicated by the value of water absorption capacity (4.7-5.7 mL/g), which greater than oil absorption capacity (1.1-1.4 mL/g). Non-enzymatic browning occurrence on okara powder samples (OD = 0.52-0.66) was more affected by the drying temperature than hydrothermal treatment. Keywords: convective drying, hydrothermal treatment, okara powder quality